Changing pictures : rock art traditions and visions in Northern Europe - Goldhahn, Joakim; Fuglestvedt, Ingrid; Jones, Andrew, 1967- (Oxbow Books, 2010)
This volume derives from a workshop held at the University of Kalmar (now Linnaeus University), Sweden between the 20-24 of October 2008. The aim of this gathering was to provide a forum for rock art researchers from different parts of northern Europe to discuss traditional as well as current interpretative trends within rock art research. Changing Pictures aims to return to traditional interpretative notions regarding the meaning and significance of rock art to investigate if and why any information had been left behind to recover and rethink. During the last decades, there has been an immense.